KEDUDUKAN LETTER C SEBAGAI JAMINAN HUTANG DITINJAU DARI HUKUM ISLAM (Ahkam: Jurnal Hukum Islam, 2024)
Collateral is one of the important principles that must be considered in debt agreements because it plays a role in providing legal certainty that the recipient of the debt will pay back his debts. Rural communities use Letter C as a substitute for land rights certificates including making them as a collateral for debt. In Islamic law, debt guarantees are included in the rahn contract. Letter C used as collateral for debt needs to be reviewed for its position so that Muslims know the validity of using Letter C as collateral for debt from the point of view of Islamic Law. What is the position of Letter C as collateral for debt in terms of Islamic law? To unravel these problems, normative legal research methods are used by collecting legal materials through library research. The result obtained is that the position of Letter C as collateral for debt in Islamic law is reviewed using a rahn contract where Letter C is allowed as collateral for debt because the Qur'an, hadith and sharia provisions do not prohibit it. Letter C may be used as collateral for debt because it complies with the principle of freedom (Al-Hurriyah) and the principle of agreement (Al-Ridha).
Keywords: Letter C; Debt Guarantee; Rahn; Islamic Law